The Epistemological Validity of Qira'at in Shahrur’s Thought: A Critical Appraisal through the Standards of Classical Qira'at Science - Sa'dullah Sa'dullah; Mia Fitriah El Karimah; Muhammad Azwar Anas (ZAD Al-Mufassirin, 2026)
This study critically evaluates Muhammad Shahrur’s claims in Nahw Usul Jadidah, which assert that Quranic qira’at variations resulted from technical codification errors in early manuscripts and ideological manipulation by classical scholars. Using a qualitative method through doctrinal-comparative analysis and source criticism, Shahrur’s framework is confronted with the epistemological standards of classical qira’at sciences, specifically the three pillars of validity (arkan al-qira’at) formulated by Ibn al-Jazari. The findings reveal a systemic epistemological failure across four layers: (1) an ontological error that disregards the tauqifi (divinely dictated) nature of qira'at; (2) a historical fallacy concerning the chronology of Hajjaj bin Yusuf’s i’jam project, wherein oral transmission was already well-established; (3) unsubstantiated allegations of sociological manipulation; and (4) the adoption of Orientalist premises that assume a document-centric fluid text while overlooking the rigorous network of oral transmission (musyafahah). The novelty of this study lies in exposing the genealogy of Shahrur’s arguments, which structurally reproduce Western historical-critical approaches using modern terminology, while identifying categorical errors in his use of classical philological sources. This research reaffirms that the integrity of qira’at mutawatir remains robust through traditional oral transmission infrastructure.